Oxidation and Acetylation of Ursolic and Oleanolic Acids Isolated from Fragraea fragrans fruits; Antiproliferation of P388 Leukemia Cells - Dasril Basir; Julinar Julinar; Eva Agustriana; Budi Untari (Indonesian Journal of Chemistry, 2014)
An interesting natural product chemistry aspect of Fragraea fragrans is that their fruits are richness with ursolic acid and its isomer oleanolic acid (3.05% of dried powder). As our continuous work on these inseparable structural isomeric triterpenes, this paper reports that 51.0% of inseparable 3-oxo-ursolic[3-oxo-oleanolic] acids and 48.6% of inseparable 3-acethyl-ursolic [3-acethyl-oleanolic] acids have already been made from those triterpenes as starting materials of the oxidized and acetylated compounds and evaluated their activity against P388 leukemia cells. The activity of 3-oxo-ursolic [3-oxo-oleanolic] acids with IC50 = 18.6 µg/mL exhibited three-fold more potent against P388 leukemia cell proliferations compared to ursolic [oleanolic] acids with IC50 = 53.5 µg/mL; while the 3-acethyl-ursolic [3-acethyl-oleanolic] acids with IC50 = 37.9 µg/mL showed two-fold more potent then their parent triterpenes (IC50 = 53.5 µg/mL) in the inhibition of P388 leukemia cell growth.